BCG-derived acellular membrane vesicles elicit antimycobacterial immunity and innate immune memory - Yamaguchi, Takehiro; Samukawa, Noriaki; Matsumoto, Sohkichi; Shiota, Masayuki; Matsumoto, Masaki; Nakao, Ryoma; Hirayama, Satoru; Yoshida, Yutaka; Nishiyama, Akihito; Ozeki, Yuriko; Tomita, Shuhei (Frontiers in Immunology, 2025)
Tuberculosis (TB) is one of the leading causes of death due to infectious disease. The sole established vaccine against TB is the Mycobacterium bovis Bacillus Calmette–Guerin (BCG) vaccine. However, owing to the lack of durable immunity with the BCG vaccine and its risk of infection, safer vaccines that can also be used as boosters are needed. Here, we examined whether membrane vesicles (MVs) from BCG (BCG-MVs) isolated from BCG statically cultured in nutrient-restricted Sauton’s medium (s-MVs) and from BCG planktonically cultured in nutrient-rich medium commonly used in the laboratory (p-MVs) could be used as novel TB vaccines. MVs are extracellular vesicles produced by various bacteria, including mycobacteria. Differences in the culture conditions affected the morphology, contents, immunostimulatory activity and immunogenicity of BCG-MVs. s-MVs presented greater immunostimulatory activity than p-MVs via the induction of TLR2 signaling. Mouse immunization experiments revealed that s-MVs, but not p-MVs, induced mycobacterial humoral and mucosal immunity, especially when administered in combination with adjuvants. In a BCG challenge experiment using BCG Tokyo type I carrying pMV361-Km, subcutaneous vaccination with s-MVs reduced the bacterial burden in the mouse lung to a level similar to that after intradermal vaccination with live BCG. Furthermore, the administration of s-MVs induced a significant lipopolysaccharide-induced proinflammatory response in macrophages in vitro. These results indicate that BCG-MVs obtained from static culture in Sauton’s medium induce not only humoral immunity against mycobacteria but also trained immunity, which can allow the clearance of infectious agents other than mycobacteria. Together, these findings highlight the immunological properties of BCG-MVs and the availability of acellular TB vaccines that confer broad protection against various infectious diseases.